Generational Gap at Damak Resort (S/O 13625) - Hassan, Hazlinda; Siam, Mohammad R.A.; Faeeq, Munadil Khaleel; Ahmad, Fais; Zuhud, Daeng Hatef Darerssalam (UUM, 2021)
The existence of three generations namely Baby Boomers, Gen X and Gen Y in the today’s workforce has caused the management of an organization to become more complex. On one hand, this phenomenon could be harmful such as conflict between different generations which is a detriment to the organization. On the other hand, it could be beneficial as well if there is a reciprocal interdependence between different generations.